2022
DOI: 10.1007/s10680-022-09613-8
|View full text |Cite
|
Sign up to set email alerts
|

Who Opts Out? The Customisation of Marriage in the German Matrimonial Property Regime

Abstract: This study examines the prevalence of marital contracts across marriage cohorts (1990–2019) in Germany. We further investigate the characteristics of spouses who signed a marital contract. Using cross-sectional data from the German Family Panel (pairfam, 2018/19), we employ complementary log–log and multinomial logistic regression models to predict the prevalence and the type of marital contracts. The results show that 5% of all married couples opt out of the default matrimonial property regime by signing a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Third, the birth of a child seems to have a negative impact on women's wealth development, while men's wealth is hardly affected by it (Lersch et al, 2017). Fourth, the matrimonial property regime seems to matter (Nutz et al, 2022). While married couples with a community property regime accumulate less wealth than married couples with a separate property regime, the gender wealth gap is smaller among couples with a community property regime (for data from France see Frémeaux & Leturcq, 2022).…”
Section: Gender Inequalities In Income and Wealth And Couples' Money ...mentioning
confidence: 99%
See 3 more Smart Citations
“…Third, the birth of a child seems to have a negative impact on women's wealth development, while men's wealth is hardly affected by it (Lersch et al, 2017). Fourth, the matrimonial property regime seems to matter (Nutz et al, 2022). While married couples with a community property regime accumulate less wealth than married couples with a separate property regime, the gender wealth gap is smaller among couples with a community property regime (for data from France see Frémeaux & Leturcq, 2022).…”
Section: Gender Inequalities In Income and Wealth And Couples' Money ...mentioning
confidence: 99%
“…While married couples with a community property regime accumulate less wealth than married couples with a separate property regime, the gender wealth gap is smaller among couples with a community property regime (for data from France see Frémeaux & Leturcq, 2022). However, married couples only very rarely opt out of the default property regime of accrued gains in Germany (Nutz et al, 2022).…”
Section: Gender Inequalities In Income and Wealth And Couples' Money ...mentioning
confidence: 99%
See 2 more Smart Citations
“…It remains unclear whether it would be generalizable to European countries with another type of default property regime, such as community of accrued gains. In Germany, where the default marital contract is the community of accrued gains, Nutz et al (2022) found that 5% of all married couples opt out of the default marital contract. Approximately half of them opt for a separate property regime, which is lower than in France or Italy.…”
Section: Generalization Of the French Casementioning
confidence: 99%